Upaya Peningkatan Keselamatan Pasien Di Pelayanan Kesehatan Primer - Guspianto, Guspianto; Amir, Andi; Justitia, Budi; Elisma, Elisma; Rahayu Ningsih, Vinna (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2025)
Adverse events remain prevalent in primary healthcare, with an estimated 24–85% considered preventable. However, their identification is hindered by limited reporting accuracy and the absence of standardized risk classification systems. This study, conducted through a Community Service Program (PkM), sought to promote patient safety culture by disseminating assessment findings, delivering educational sessions, and facilitating case-based discussions. Evaluation results demonstrated improved knowledge among community health center (Puskesmas) staff regarding patient safety culture and strategies for its enhancement. To strengthen patient safety, Puskesmas management is advised to optimize staff workload allocation, enhance competence and capacity, foster open communication, ensure a non-punitive reporting environment, and implement accessible, user-friendly reporting systems. Sustained application of these strategies is essential for continuous improvement in healthcare quality and patient safety.